Strain evaluation using a non-contact deformation measurement system in tensile tests of irradiated F82H and 9cr ODS steels. (August 2018) - Sakasegawa, Hideo; Chen, Xiang; Kato, Taichiro; Tanigawa, Hiroyasu; Ando, Masami; Geringer, Josina W.; Ukai, Shigeharu; Ohtsuka, Satoshi
Highlights: Non-contact deformation measurement system was developed. More accurate stress strain curves were obtained for irradiated specimens. Dynamic deformation behavior was obtained and it was helpful for verifying test result. Abstract: We developed a non-contact deformation measurement system to accurately evaluate strain for post irradiation tensile testing, since conventional strain gages cannot be used for small size specimens. The strain calculated from cross-head displacement generally includes deformation from specimen shoulders, fixtures, and the test frame in addition to the deformation from the specimen gauge section. In our system, the distance between painted marks within the specimen gauge section was measured using a high resolution video camera to evaluate the specimen deformation during room temperature tensile testing. The test materials were F82H and 9Cr ODS steels irradiated up to ≈71 displacements per atom (dpa) at about 573 K in High Flux Isotope Reactor (HFIR) at Oak Ridge National Laboratory (ORNL). Our system yielded accurate stress strain curves without deformations other than the specimen gage section, and the elongation was less than that calculated from cross-head displacement. This system can contribute to expanding the technically reliable database for the design activity of fusion reactor blanket, including the effects of irradiation on tensile properties.